How often are gonorrhoea and genital yeast infection sexually transmitted? - Thin, R N (1979)
Although gonorrhoea is often regarded as the sexually transmitted disease against which others are measured, its infectivity is not clearly understood. Estimates of the infection rate have varied from 5--90%. In this study, 50 couples with gonorrhoea were matched with 50 couples with genital yeast infection. Gonorrhoea was diagnosed in both partners of 32 couples and genital yeast infection in both partners of 21 couples. These figures provide an indication of the sexual transmission of these conditions. The higher figure for gonorrhoea may be related to a greater urgency in tracing contacts.